Implementation of Government Regulation Number 42 of 2007 Regarding Franchise Agreements in Local Fast Food Businesses - Savirra Satriadi; Etty Mulyati; Tri Handayani (Universitas Muhammadiyah Sumatera Utara, 2023)
Franchising is one of the opportunities to become an entrepreneur, which recently is one of the developing economic activities. Franchise itself is a special right owned by an individual or business entity with business characteristics in order to market goods and/or services based on a franchise agreement. Franchise Agreements have implications for Local Warteg Franchise and Japanese Udon Foreign Franchise. The purpose of this research is to know and understand the Domestic Franchise Agreement and Foreign Franchise and to know and understand the Implementation of Government Regulation Number 42 of 2007 Regarding Franchise Agreements in Local Fast Food Businesses. The research method used is descriptive with a normative juridical research type using a statutory approach (Statute Approach) then data collection techniques through document studies on secondary data, then the data is analyzed with qualitative juridical. Based on the results of the study it was concluded that the Object of Research on Local Fast Food Franchise Agreements, namely domestic franchises, namely Warteg and Japanese Udon Foreign Franchises both made by the nation's children and foreign franchises still refer to positive law in Indonesia, namely Government Regulation 42 of 2007 concerning Franchising , then the Implementation of Government Regulation Number 42 of 2007 regarding Franchise Agreements on Local Fast Food is specifically regulated in Article 5 of Government Regulation Number 42 of 2007 concerning Franchising Other than Clauses that must be in the Franchise Agreement, one of the legal instruments that must be observed is STPW.